The Role of Macrophage Class A Scavenger Receptors in a Laser-Induced Murine Choroidal Neovascularization Model - Jawad, Shayma (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. Laser-induced choroidal neovascularization (CNV) is a widely used model to mimic many features of CNV resulting from wet AMD. Macrophages have been implicated in the pathogenesis of AMD. Class A scavenger receptors, scavenger receptor-A (SR-A) and macrophage receptor with collagenous domain (MARCO), are expressed on macrophages and are associated with macrophage function. The goal of this study is to examine the role of macrophage scavenger receptors in immune cell recruitment and the formation of CNV. METHODS. Laser photocoagulation was performed in wild-type and knockout mice with deletion of SR-A (SR-A(−/−)), MARCO (MARCO(−/−)), or both SR-A and MARCO double knockout (DKO). Immune cell recruitment at different time points and CNV lesions at 14 days after laser treatment were evaluated through immunostaining and confocal microscopy. Microarray analysis was performed in eyes 1 day after laser injury. RESULTS. Wild-type eyes showed higher chemokine/receptor expression compared with knockout eyes after laser injury. Scavenger receptor deficiency markedly impaired the recruitment of neutrophils and macrophages to CNV lesions at 1- and 3-days post laser injury, respectively. Significantly reduced CNV volumes were found in the eyes from scavenger receptor knockout mice compared with wild-type mice. CONCLUSIONS. The deficiency of scavenger receptors impairs the formation of CNV and immune cell recruitment. Our findings suggest a potential role for scavenger receptors in contributing to CNV formation and inflammation in AMD.